The Effect of Leadership and Organizational Culture on Employee Performance through Job Satisfaction as Mediation at Pakuwon Sumedang General Hospital during the COVID-19 Pandemic - Annissa Noeradiana; Imma Ismaniar (Politeknik Mardira Indonesia, 2024)
Health workers experience high work pressure during the pandemic due to an increase in the number of patients. Pakuwon Sumedang General Hospital also experienced this. In a situation like this, employee performance in the health sector becomes essential. Several factors can affect employee performance in the health sector, such as the role of leadership, organizational culture, and job satisfaction. This study aims to determine the influence of leadership and organizational culture on employee performance by mediating job satisfaction at Pakuwon Sumedang General Hospital during the pandemic. This research is a descriptive verification study by distributing questionnaires to 70 employees of Pakuwon Sumedang General Hospital. Research testing using descriptive analysis and path analysis. The analysis results show that leadership and organizational culture can influence employee job satisfaction by 87.4%. The rem variables outside this model can influence the remaining 12.6%yee performance can be affected by leadership by 50.55% and influenced by organizational culture by 7.08%. Partially, leadership significantly affects job satisfaction, and organizational culture significantly affects job satisfaction. In addition, partially, leadership significantly affects employee performance, and organizational culture significantly affects employee performance.